PROTEIN-PROTEIN INTERACTIONS: METHODS AND BIOLOGICAL SIGNIFICANCE (International Journal of Food and Nutritional Sciences, 2021)
This study explores various experimental techniques employed to investigate PPIs, emphasizing their contributions to advancing our understanding of complex cellular processes. Protein-protein interactions (PPIs) are fundamental to the architecture and function of biological systems, governing processes essential for cellular homeostasis, signal transduction, metabolic regulation, and more. Understanding the methods used to study PPIs is crucial for unraveling their biological significance and their implications in health and disease. High-throughput methods such as yeast two-hybrid screens, co-immunoprecipitation coupled with mass spectrometry, and protein microarrays enable systematic identification and characterization of PPI networks. These approaches provide insights into the dynamic nature of interactions, their specificity, and the contexts in which they occur. Structural biology techniques, including X-ray crystallography, NMR spectroscopy, and cryo-electron microscopy, elucidate the atomic details of protein complexes, revealing how interactions dictate molecular recognition and functional outcomes. Computational methods, such as molecular docking, molecular dynamics simulations, and network analysis, complement experimental data by predicting PPIs, modeling complex dynamics, and integrating large-scale interaction networks with other omics data. Biologically, PPIs drive diverse cellular functions, from regulating gene expression and coordinating metabolic pathways to mediating immune responses and maintaining cellular structure. Examples include the role of signaling complexes in transmitting extracellular signals, the assembly of enzymatic complexes for metabolic flux regulation, and the formation of structural scaffolds that support cellular architecture.